2010
DOI: 10.1088/2040-8978/12/7/075101
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two-dimensional photonic crystal L-type cavities with low-refractive-index material cladding

Abstract: We have theoretically investigated two-dimensional photonic crystal (2D PC) L1–L21 cavities with low-refractive-index (low-n) material cladding using the 3D finite-difference time domain method assisted by group theory in the time domain. We investigated various optical properties of 2D PC L-type cavities including resonant frequency, modal symmetry, Q factor, modal volume, real-space distribution, wavevector-space distribution and resonant wavevector condition. The resonant modes in 2D PC L-type cavities are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 41 publications
5
39
0
Order By: Relevance
“…15, showing the numerically computed resonant frequencies (a) and threshold gain ((b), solid curve); each colour corresponds to a different longitudinal resonant mode. In the existing literature, similar cavities have been studied in [4] through FDTD simulations. In [4], it has been shown that the resonant modes of a passive LN cavity correspond to the fullfillment of the condition (0.5 − k z a/2π) = m/2N (10) with N = L/a being the number of unit cells, m the mode order and k z the dispersion relation of the passive PhC LDWG of the cavity.…”
Section: B Phc Lasersmentioning
confidence: 99%
See 2 more Smart Citations
“…15, showing the numerically computed resonant frequencies (a) and threshold gain ((b), solid curve); each colour corresponds to a different longitudinal resonant mode. In the existing literature, similar cavities have been studied in [4] through FDTD simulations. In [4], it has been shown that the resonant modes of a passive LN cavity correspond to the fullfillment of the condition (0.5 − k z a/2π) = m/2N (10) with N = L/a being the number of unit cells, m the mode order and k z the dispersion relation of the passive PhC LDWG of the cavity.…”
Section: B Phc Lasersmentioning
confidence: 99%
“…In the existing literature, similar cavities have been studied in [4] through FDTD simulations. In [4], it has been shown that the resonant modes of a passive LN cavity correspond to the fullfillment of the condition (0.5 − k z a/2π) = m/2N (10) with N = L/a being the number of unit cells, m the mode order and k z the dispersion relation of the passive PhC LDWG of the cavity. For this reason, we have evaluated the quantity 0.5 − β eff a/2π at the numerically computed resonant frequencies and corresponding threshold gain of Fig.…”
Section: B Phc Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to these as odd and even Fabry-Pérot (FP) modes because the line defect with 39 missing air holes can essentially be regarded as a FP cavity. [26][27][28][29] It should be emphasized that, in general, only the resonant modes associated with the even-propagation mode have been examined in studies on Raman Si lasers. 30,31 Here we additionally focus on the resonant modes that arise from the odd-propagation mode.…”
Section: Sample Structurementioning
confidence: 99%
“…Many impressive achievements have already been reported, including measured quality (Q) factors exceeding a few million [4,5], flat-band slow light by dispersion engineering [6,7], enhanced nonlinearities [8] and slow-light enhanced gain [9]. By omitting only a finite number (N) of air-holes in a line, a so-called LN-cavity can be realized [10]. Compared to conventional Fabry-Perot or DFB edge-emitting lasers, such micro cavity lasers have many interesting characteristics, such as ultra-small size, with the possibility of close-to-diffraction-limited mode volume, ultra-low threshold, and on-chip integration [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%